Cholesterol Homeostasis and Liver X Receptor (LXR) in Atherosclerosis - Guo, Shuyuan; Li, Luxiao; Yin, Huiyong (Cardiovascular & Haematological Disorders - Drug Targets, 2018)
Cholesterol is an important lipid for maintaining cell membrane fluidity and generation of various hormones and bile acids. Thus, it is critical to maintain cholesterol homeostasis including absorption, trafficking, biosynthesis, and efflux; dysregulation of cholesterol homeostasis may lead to human disorders such as atherosclerosis. As a cholesterol sensor, nuclear receptor liver X receptor (LXR) is an important factor regulating cholesterol homeostasis. Extensive research has been carried out to examine the roles of LXR in atherosclerosis. In this review, we summarize our current understanding of the mechanisms how LXR regulates cholesterol synthesis, efflux, absorption, and conversion of cholesterol esters to cholesterol in the context of atherosclerosis. In addition, we also discuss the possibility of targeting LXR and cholesterol homeostasis as a potential interventional strategy for treating atherosclerosis.
Keywords: CVD